Parent's Education and Economics on Children Literacy Skills in the Pandemic Times - Noor Baiti (Universitas Musamus, Faculty of Teacher Training and Education, 2021)
Children's literacy skills are related to language skills in writing and reading. During pandemic times parents are required to meet facilities and guide children at home. The education and economics of parents play a role in this situation. The purpose of this study is to find out the educational and economic influence of parents on children's literacy skills. This research used quantitative research. This research used a questionnaire instrument, observation, and interviews in data collection. The results of this study indicate: (1) the influence of parental education on the literacy ability of early childhood, (2) the influence of the economy of parents on the literacy ability of early childhood, and (3) the influence of parents' education and economy on early childhood literacy skills.